Analysis Sentiment of Twitter User on Indonesia's 2024 Presidential Election Using K-Means Algorithm - Leny Tritanto Ningrum; Dwi Rahmiyati (JURNAL SISFOTEK GLOBAL, 2023)
The General Election is a five-year agenda of the Indonesian people in order to fulfill the political rights of every citizen for the election of the president and the legislature. In every election, especially during the campaign period, differences of opinion often occur between certain groups or factions, this often creates an atmosphere of political uproar in various parts of Indonesia. The purpose of this study is to see the level of sentiment of social media users towards the implementation of elections in Indonesia so as to minimize political upheaval that occurs in society during the elections to be held in 2024. The data that will be used in this research is data on Twitter users who have large volumes and are taken from all regions of Indonesia. To suit the data model used, this study will use the data mining method with the K-Means algorithm. The results of this study show the percentage level of public sentiment of Twitter users towards the 2024 election and presidential election. Public sentiment is positive, neutral and negative. Based on these results, it can provide input to the government so that it can make appropriate policies ahead of elections and presidential elections so as to create a peaceful atmosphere.